Conferências de políticas públicas e inclus\~ao participativa - Eleonora Schettini M. Cunha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The paper presents an exploratory study aims to verify the potential of public policy conferences for the inclusion of population segments that have been traditionally excluded from political participation processes, such as women, blacks, illiterates, low schooling and less income. The study indicates that the scale is relevant to some factors, as well as the type of public policy. It also points to the necessary consolidation and expansion of such studies, so they can produce more consistent and generalizable information.
Keywords: Z18; 330; public policy conferences; participation; inequality